The Role of Leverage Mediation on the Relationship of Capital Structure to Firm Value in the Mining Sector - Lukman Setiawan; Sitti Mujahida Baharuddin; Abdul Haris; Partono Soemarno; Andi Yusran Paris (Universitas Dharma Wacana, 2022)
This study aims to examine the role of leverage as a mediator of the effect of capital structure on firm value, as well as to partially examine the capital structure of leverage and firm value in the mining sector listed on the Indonesia Stock Exchange. The population in this study amounted to 62 companies obtained using the purposive sampling method during the 2019-2021 period and based on predetermined criteria, a sample of 14 companies was obtained from 2019-2021 so that the total sample was 42 observation periods. In solving problems and hypotheses, method used is path analysis.The results of the study show the role of leverage as a perfect mediator, in the sense that the effect of capital structure on firm value is largely determined by leverage, then partially capital structure, leverage has no significant effect on firm value, but the effect of capital structure on leverage has a positive and significant effect on the mining sector. on the Indonesia Stock Exchange for the period 2019-2021.